SELF-EFFICACY BELIEFS AMONG INDIVIDUALS WITH DEPRESSION: A FUNCTION OF CREATIVITY-BASED POSITIVE PSYCHOTHERAPY - Sukaina Kasem; Sidra Farooq Butt (Pakistan Journal of Clinical Psychology, 2022)
Objectives: The current research aims to explore the efficacy of a Creativity-based Positive Psychotherapy intervention in treating low levels of Self-Efficacy among individuals with depression; subsequently, the study further attempts to examine the intervention’s overall effects on Depression (through the mediation of Self-Efficacy). The Design of The Study: The study has a quantitative Pre-test Post-test quasi Experimental research design. Place and Duration of the study: Karachi, Pakistan; March, 2020 – October, 2020. Sample and Method: A purposive snowball sampling technique has been used to recruit N=10 young adults, age ranging from 18 to 30 years, who were experiencing low levels of Self-Efficacy due to Depression in addition to having low Creativity levels. It is hypothesized that the Creativity-based Positive Psychotherapy intervention will positively affect Self-Efficacy, have a subsequent negative effect on Depression and that there will be a significant difference between those participants who will receive the intervention and those from the waiting-list control group. To test the hypotheses, the data has been collected through the Patient Health Questionnaire (PHQ), the General Self-Efficacy Scale (GSE); and the Short Scale for Creative Self (SSCS). The Paired Sample and Independent Sample t-tests were utilized to analyze the hypotheses using the Statistical Package for Social Sciences, version 22 (SPSS V.22). Results and Conclusion: The results of the study supported the proposed hypotheses and confirmed the effectiveness of the Creativity-based Positive Psychotherapy intervention in treating low Self-Efficacy (p<.05), as well as, Depression (p<.05) within individuals experiencing mild to moderate depression.